The functionality of folk narratives in the reproduction of culture in the context of the legends “kizilirmak” and “karakoyun” [“Kizilirmak” ve “karakoyun” efsaneleri bağlaminda kültürün yeniden üretiminde halk anlatilarinin işlevselliği] - (:unkn) unknown (Milli Folklor Dergisi, 2020)
Folk narratives are used as a source for modern genres sometimes in the form of intertextuality and sometimes in the form of reproduction/creation. Some motifs or episodes undergo change and transformation while reproduction is based on folkloric or traditional elements. There are different reasons for the reproduction of folk narratives in modern literary genres. For example, folk narratives can be instrumentalized to arouse national consciousness and build national identity; it is aimed to introduce folkloric elements/values, which are about to disappear in modern society, to modern individuals. The reproduction of folklore is also exemplified by the works created from the myths/folk narratives of “Kızılırmak” and “Karakoyun”. Three films were made through the combination of both folk narratives. Nazım Hikmet’s script which is based on these folk narratives was filmed by Muhsin Ertuğrul in 1947. Again, based on this folk narrative, Yılmaz Güney wrote a script, which was filmed in 1967 by Ömer Lütfi Akad. Tuncer Cücenoğlu, who wrote the script of the film which was filmed for the third time in 1992, also benefited from the previous works, which was filmed by Şahin Gök. Cücenoğlu transforms these folk narratives into a musical play called Kızılırmak. In these works, which are an example of the reproduction of culture based on folk narratives and folkloric elements, the values, which were about to disappear and which were used as a source of folklore, were rebuilt with a modern form and discourse, and at the same time, the collective subconscious of the nation to which these folk narratives belonged were attempted to be enlightened. Although there were many changes/transformations in the source texts during the reproduction of the folkloric elements, the main episodes were mostly preserved. The form, discourse and theme of anonymous folk literature such as folk songs and mani (Turkish poem or song) were imitated in the script texts and especially in verse texts in which the folk narratives were used as direct sources. While there is no direct relationship between the two narratives formed around Kızılırmak and Karakoyun, both legends are combined in the modern texts created in the process of reproduction based on these narratives. Particularly in cinema films, both myths were skilfully placed in the texture of the text to form a composition. There has not been a study about the reflections of folk narratives formed around Kızılırmak and Karakoyun in modern literature and art. This article examines how folkloric elements and folk narratives constitute a source for modern texts. First of all, folk narratives and common episodes in modern narratives have been investigated; then, it has been evaluated that how the folk narratives have been used as subject, form and discourse in the production of films and plays based on these folk narratives. During this study, it was realized that the effect of folklore on modern literary genres, especially in modern Turkish theatre, has been very few on the traces of folklore or folk narratives. As a consequence of this study, it is aimed to make a contribution to the researches in this field. © 2020, Milli Folklor Dergisi. All rights reserved.
Keywords: Cinema; Folk narratives; Legend; Reproduction; Theatre